Sleep disorders and obesity in adolescents: peculiarities of psycho-cognitive status (literature review) - O. N. Berdina; L. V. Rychkova; I. M. Madaeva (Acta Biomedica Scientifica, 2017)
Adolescence is a time of important physical, cognitive, emotional, and social changes. Sleep is a primary aspect of adolescent development. Its disorders critically influence adolescents' ability to think, behave, and feel during daytime hours. Daytime activities, changes in the environment, and individual factors can have significant effects on adolescents' sleeping patterns. It is known, that a significant change of the sleep-wake cycle across adolescent development is a tendency to stay up later at night and to sleep in later in the morning. The peculiarity of this period of life is called a sleep delayed phase phenomenon, which can play the important role in the development of eating disorders and cause risk of obesity. The epidemic of childhood obesity presents a major public health problem. Many authors consider that obesity is a multisystem disease with potentially devastating consequences for physical and emotional health across the lifespan. Obesity may cause obstructive sleep apnea syndrome that can result in excessive daytime sleepiness in adolescents and have a negative effect on learning, school performance, and behavior. Early detection of risk factors, screening for metabolic and sleep disturbances in adolescents are major aims in reducing risk of cognitive and behavioral disorders. We assume that further studies of the psycho-cognitive impairments in adolescents with obesity in the sleep-wake continuum are necessary for the development of new approaches to forecasting, early diagnosis and pathogenically therapies of emotional and cognitive changes at the stage of personality formation as well as potentially reversible sleep and metabolic disorders.